Protected Children, Regulated Mothers : Gender and the "Gypsy Question" in State Care in Postwar Hungary, 1949-1956 - Varsa, Eszter, 1975- (Book collections on Project MUSE., 2021)
"Protected Children, Regulated Mothers examines child protection in Stalinist Hungary as a part of twentieth-century (East Central, Eastern, and Southeastern) European history. Across the communist bloc, the increase of residential homes was preferred to the prewar system of foster care. The study challenges the transformation of state care into a tool of totalitarian power. Rather than political repression, educators mostly faced an arsenal of problems related to social and economic transformations following the end of World War II. They continued rather than cut with earlier models of reform and reformatory education. The author's original research based on hundreds of children's case files and interviews with institution leaders, teachers, and people formerly in state care demonstrates that child protection was not only to influence the behavior of children but also to regulate especially lone mothers' entrance to paid work and their sexuality. Children's homes both reinforced and changed existing patterns of the gendered division of work. A major finding of the book is that child protection had a centuries-long common history with the "solution to the Gypsy question" rooted in efforts towards the erasure of the perceived work-shyness of "Gypsies.""--